Plasmodium vivax Duffy binding protein: a modular evolutionary proposal (2004)
The population of malaria-causing parasites is characterized by great genetic diversity. Knowledge of the polymorphism generation mechanism is a central issue for developing effective vaccines against malaria and understanding the parasite population structure. Plasmodium vivax genetic diversity has been explained in terms of two major factors: natural selection and intragenic recombination. A modular organization was found within P. vivax Duffy binding protein in the present work. Four Colombian isolates have identical sequences to Salvador-1 strain amongst dpb regions III–VI analysed, suggesting a high identity between Central and South American isolates. Geographically clustered sectors, corresponding to cysteine-rich regions (II and VI), show a high sequence diversity that could reflect a possible immune response evasion mechanism; both positive and negative selection were detected in these regions. In contrast, other dbp gene regions display a non-geographical clustering pattern, lower sequence diversity and predominant negative selective pressure. Recombination was homogeneously detected all along the molecule. These findings suggest that diversification vs. homogenizing forces, drive dbp gene evolution and determine its mosaic region organization.